Maybe you should talk to someone a therapist, her therapist, and our lives revealed - Gottlieb, Lori; Pressley, Brittany (Tullamarine, Victoria Bolinda Audio, 2019)
Meet Lori Gottlieb, an insightful and compassionate therapist whose clients present with all kinds of problems. There's the struggling new parents; the older woman who feels she has nothing to live for; the self-destructive young alcoholic; and the terminally ill 35-year-old newlywed. And there's John, a narcissistic television producer, who frankly just seems to be a bit of a jerk. Over the course of a year, they all make progress. But Gottlieb is not just a therapist, she's also a patient who's on a journey of her own. Interspersed with the stories of her clients are her own therapy sessions, as Gottlieb goes in search of the hidden roots of a devastating and life-changing event. Personal, revealing, funny, and wise, Maybe You Should Talk to Someone opens a rare window onto a world that is most often bound by secrecy, offering an illuminating tour of a profoundly private process.
Compact disc, MP3 format.
Read by Brittany Pressley.
System requirements: Requires the use of an MP3 enabled CD player or computer.
107323
Keywords: Gottlieb, Lori -- Health; Psychotherapists -- Biography; Therapist and patient -- Biography; Health; Audiobooks; Autobiographies; Biography